2011
DOI: 10.1002/term.449
|View full text |Cite
|
Sign up to set email alerts
|

Vascular tissue construction on poly(ε-caprolactone) scaffolds by dynamic endothelial cell seeding: effect of pore size

Abstract: In vitro tissue engineering for fabrication of small diameter vascular grafts probably undergoes a sequence of events similar to the in vivo angiogenesis process. In both cases endothelial cells (ECs) play the crucial role in generating a non-thrombogenic vessel lumen and stabilization of ECs in the lumen of new vessels requires the deposition of collagen IV and elastin. Shear stress is an important in vivo signal for inducing synthesis of extracellular matrix (ECM) components, collagen IV and elastin, which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
(32 reference statements)
0
14
0
1
Order By: Relevance
“…1a). It was demonstrated that smaller pores in scaffolds could improve ECs proliferation 25 . Conversely, larger pores (60–150 μm) in the outer layer could aid SMCs cultivation, infiltration and proliferation 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). It was demonstrated that smaller pores in scaffolds could improve ECs proliferation 25 . Conversely, larger pores (60–150 μm) in the outer layer could aid SMCs cultivation, infiltration and proliferation 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the best hemocompatibility is obtained when the luminal surface is coated with healthy endothelial cells that facilitate blood flow and prevent thrombosis 22, 23 , while the presence of functional SMC within the medial layer of vascular wall facilitates certain functions such as vasoconstriction and relaxation as well as secretion of vasoactive regulators 21, 24 . Smaller pores are more suitable for ECs to create a monolayer on the luminal surface of the scaffold while SMCs require interconnected pores above 60 micrometers in diameter to proliferate and build a muscular media 24, 25 . Therefore, an ideal vascular scaffold must provide the suitable requirements for the growth of both cell types.…”
Section: Introductionmentioning
confidence: 99%
“…In the perspective of biodegradable 3D stent, the mask-projection excimer laser stereolithography allows not only fabricating stents with the proper macrogeometry (diameter, length/height, and meshed shape), but also controlling the morphology on the microscale. The selection of appropriate scaffold architecture with suitable pore mesh has long been recognized as the key factor that may influence the mechanical strength and determine tissue remodelling [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that elastin promotes in vivo endothelial cells adhesion and proliferation [27], which are responsible for all those mechanisms that regulate the platelet and smooth muscular cells overgrowth [28]. In particular, elastin displays a natural antithrombotic effect, which prevents the new obstruction of blood vessels [2, 18, 29]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation